(3TQM GdTGajIs - (3fLe GdOjf QVi GdOjf eMeO Hf GdMSf GdCSJQGHGPi GdfMhis; (3GHf GdMGLH , LeGd GdOjf CHh YeQh GHf GdMGLH, LeGd GdOjf CHh YeQh GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3CeG HYO MeOkG ddg JYGdi hHYO abO GdJeS efi ef dGjSYfi eNGdaJg Cf CdMb HebOeJj ai GdCYQGH ebOeI ai GdJUQja GdJUQja Yde HCUhd Gbhd bhdg HGUhd jYfi HgG GdbhGfjf s
(3BNQgG (B:s
(3hbO eQ GdcdGe Ydjg ai HGH GdGeGdI bhdg Hdi Pdc dGeGdJgG hGdi hYdi dbhdge Gdjc hYdjc hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1021s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdUQas